2019
DOI: 10.1111/jvh.13246
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of transient elastography, point shear wave elastography, APRI and FIB‐4 for staging liver fibrosis in chronic viral hepatitis

Abstract: Ultrasound‐based elastography and serum indexes have been individually validated as noninvasive methods for staging liver fibrosis in chronic viral hepatitis. We aimed to compare the accuracy of transient elastography (TE), shear wave elastography (SWE), aspartate aminotransferase to platelet index (APRI) and Fibrosis‐4 index (FIB‐4) with the METAVIR liver fibrosis staging in viral hepatitis patients. We enrolled 121 treatment‐naïve chronic hepatitis B and C monoinfected patients. All underwent liver biopsy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
3
25
2
1
Order By: Relevance
“…13 Hyperglycaemia might increases risks of adverse outcome. APRI score was initially developed as a noninvasive model for fibrosis and cirrhosis diagnosis, 32,33 which has been shown to be useful for the assessment of advanced liver fibrosis in a variety of liver diseases, such as chronic viral hepatitis [33][34][35] and non-alcoholic fatty liver disease (NAFLD). 36 In an American study, APRI levels were associated with increased mortality from liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 Hyperglycaemia might increases risks of adverse outcome. APRI score was initially developed as a noninvasive model for fibrosis and cirrhosis diagnosis, 32,33 which has been shown to be useful for the assessment of advanced liver fibrosis in a variety of liver diseases, such as chronic viral hepatitis [33][34][35] and non-alcoholic fatty liver disease (NAFLD). 36 In an American study, APRI levels were associated with increased mortality from liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…These HCV RNA-positive individuals have been described in more detail elsewhere. 30 We present results of multivariate analysis in the form of Forrest plots generated using Microsoft Excel v. 16.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] GPR has recently been reported as an independent predictor of significant fibrosis in naive Gambian patients with chronic hepatitis B (CHB) infection, 13 while the usefulness of cut-off values for APRI scores in CHB has been questioned. 16 However, further studies are needed to determine the specificity and sensitivity of different scores in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Several serological tests have been established to identify liver fibrosis. The aspartate aminotransferase to platelet ratio index (APRI) and fibrosis-4 index (FIB-4) scoring are the most extensively used compound substitutes for detecting progressive fibrosis (16) . Uroš Karić et al concluded in their study that FIB-4 was superior to APRI in distinguishing severe fibrosis.…”
Section: Introductionmentioning
confidence: 99%